Effectiveness of Self-Control and Cyberloafing on Employee Performance: The Study of CV Galiya Corp. - Hafizh, Levana Bening; Sumadhinata, Yelli Eka (Universitas Proklamasi 45, 2023)
The development of technology, computers, and telecommunications supports the development of internet technology at this time, especially for business people. The convenience of the internet in doing business serves as a tool for exchanging information electronically into an application tool as a business strategy. With the ease of using the internet in business, especially in companies, it is undeniable that there are advantages. The purpose of this study was to examine and analyze the effect of self-control and cyberloafing on employee performance. This study uses primary data by taking the population used in the study to select a company. CV Galiya Corp. which is located in Bekasi City uses 40 respondents who work in the company. The method used is a type of quantitative research with survey methods. Data collection techniques by using questionnaires to respondents' employees' CV Galiya Corp lives or offline. The data processing method in this study uses SPSS 25 software which is used in testing the validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple regression analysis, t-test, and f test. The results show that the self-control and cyberloafing variables simultaneously affect the employee performance variable. The self-control variable is the most dominant in influencing employee performance in CV Galiya Corp.